A new genus and two new species of Opilioacaridae (Acari: Parasitiformes) from Amazonia, Brazil with a key to world genera - Vázquez, Ma. Magdalena; de Araújo, Marcel Santos; Feres, Reinaldo José Fazzio (Zootaxa, 2014)
Collections of Opilioacaridae made close to 50 years ago in Manaus in the Amazonian Region have allowed the description of a new genus and two new species from Brazil, Amazonacarus setosus n.gen, n.sp. and A. paraensis n.gen, n.sp. These species show a unique combination of characters in the Opilioacaridae: a high number of foliate setae (10) on the palp tarsus with each seta bearing many lobes (6–7), a group of large, serrate setae (26–31) on the palp tibia (this group of setae is much smaller in other species), and 5–7 dorsal setae on idiosomal segment XVIII. Indiacarus and some Opilioacarus show 3–5 setae on segment XVIII, but these genera (and Caribeacarus) have fewer foliate setae on the palp (3–4). Females of Amazonacarus have an ovipositor of the “complex” type, with spiny projections and 2–4 genital setae, while males have two pairs of rounded, large glands.